Pembandaran, perubahan atmosfera bandar dan persepsi manusia di bandaraya Ipoh,Perak - Mohd Hairy Ibrahim (Tanjong Malim, 2014)
Pembandaran, perubahan atmosfera bandar dan persepsi manusia di bandaraya Ipoh,Perak by Mohd Hairy Ibrahim